Hole‐Accepting‐Ligand‐Modified CdSe QDs for Dramatic Enhancement of Photocatalytic and Photoelectrochemical Hydrogen Evolution by Solar Energy. Issue 4 (2nd December 2015) - Li, Xu‐Bing; Liu, Bin; Wen, Min; Gao, Yu‐Ji; Wu, Hao‐Lin; Huang, Mao‐Yong; Li, Zhi‐Jun; Chen, Bin; Tung, Chen‐Ho; Wu, Li‐Zhu
Abstract : Solar H2 evolution of CdSe QDs can be significantly enhanced simply by introducing a suitable hole‐accepting‐ligand for achieving efficient hole extraction and transfer at the nanoscale interfaces, which opens an effective pathway for dissociation of excitons to generate long‐lived charge separation, thus improving the solar‐to‐fuel conversion efficiency.